2004
DOI: 10.7164/antibiotics.57.590
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Antibiotic Siomycin on Antibody Production

Abstract: The antibiotic thiazole compound siomycin, which we have found from the culture broth of Actinomycetes (strain No.806097) in search of antibody production inhibitor, showed the in vitro immunosuppressive property against B-cells stimulated with T-cell independent antigen DNP-LPS (dinitrophenyl-lipopolysaccharide) while it also showed inhibitory effect against Tcell proliferation. Its inhibitory mechanism was considered to be different from that of FK506, the representative of T-cell immunosuppressant. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
6

Year Published

2009
2009
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 10 publications
1
19
0
6
Order By: Relevance
“…In contrast, results show no in vivo suppression of anti-DNP antibody production by FK506 and cyclosporine A. Our results complete a previous in vitro study reporting the insufficient inhibitory potency of FK506 on DNP-LPS-stimulated B cells [29]. Suzuki et al also reported no antibody suppression by both FK506 and cyclosporine A in human B cell cultures in the absence of T cells [30].…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, results show no in vivo suppression of anti-DNP antibody production by FK506 and cyclosporine A. Our results complete a previous in vitro study reporting the insufficient inhibitory potency of FK506 on DNP-LPS-stimulated B cells [29]. Suzuki et al also reported no antibody suppression by both FK506 and cyclosporine A in human B cell cultures in the absence of T cells [30].…”
Section: Discussionsupporting
confidence: 70%
“…[7][8][9][10] Beyond its ensuing strong antibacterial activity on Gram-positive organisms, [4,7] 1 has also been reported to display potency against the malaria parasite [11] and selected tumor cell lines, [12,13] and to have immunosuppressant properties. [14] Here we describe a fluorescent high-affinity probe derived from 1 that allows the interaction of thiopeptides with their target to be quantified.…”
mentioning
confidence: 99%
“…[51] Sie wirkt, ähnlich wie viele andere Thiopeptid-Antibiotika, durch Binden an die 23S-Region der bakteriellen ribosomalen RNA und an das Protein L11, wodurch die GTPase-abhängige Funktion der ribosomalen 50S-RNA gestört und die Proteinbiosynthese unterbunden wird. [52] Der Biosyntheseweg zu Thiostrepton wurde intensiv untersucht, und der mutmaßliche Reaktionsweg über eine Diels-Alder-Reaktion [46b] inspirierte die Gruppe von Nicolaou [53] bei ihren Versuchen, den Dehydropiperidinkern des Moleküls aufzubauen.…”
Section: Thiostreptonunclassified